Determinants of treatment outcomes in pediatric patients with acute rhinosinusitis caused orbital complications: observational study - Ulashev, Shukhrat Makhmudovich; Mahmudova, Saodat Kurbonbekova; Khushvakova, Nilufar Jurakulovna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The aim of the study was to identify predictors of disease severity and describe the characteristics of orbital complications as the direct result of ARS in children. Methods: Through retrospective study, we investigated 78 children with stage I-IV orbital complications between 2005 and 2020 in regional multidisciplinary children's medical center. Samples were obtained for the microbiological analyses. Statistical tests and descriptive statistical methods were used. Results: The research included 78 children who were hospitalized for orbital complications after ARS. There were 44 male patients (56.4%), with a sex ratio of 1.29:1. Staphylococcus aureus was cultured in 31 (34.8%) of patients, followed by Streptococcus pyogenes in 26 (29.2%). We found a significant association between age, severity of complications and treatment outcomes. The age of over seven years was associated with more severe orbital complications (stage II-III) and the need of surgical intervention (p<0.001). Pre-clinical antibiotic administration had no significant influence on illness severity at the time of presentation (p=0.38). Conclusions: In this study, severe orbital complications and the age of over seven years were determinants the antibiotic failure. Clinicians should consider early referral of children older than seven years with orbital complications for better treatment outcomes.